1994
DOI: 10.1172/jci117549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relaxin on mast cells. In vitro and in vivo studies in rats and guinea pigs.

Abstract: The results of the current study demonstrate that relaxin inhibits histamine release by mast cells. This effect is related to the peptide concentrations, and could be observed in both isolated rat serosal mast cells stimulated with compound 48/ 80 or calcium ionophore A 23187, and in serosal mast cells isolated from sensitized guinea pigs and challenged with the antigen. The morphological findings agree with the functional data, revealing that relaxin attenuates calcium ionophore-induced granule exocytosis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 33 publications
(28 reference statements)
5
51
0
Order By: Relevance
“…In the heart, NO may be generated by various components of the coronary vessels, such as endothelium and smooth muscle cells (Palmer et al, 1988;Mollace et al, 1991), as well as by perivascular mast cells (Masini et al, 1991). In this context, it should be mentioned that mast cells and vascular smooth muscle cells have been shown by us to increase NO production upon RLX treatment (Masini et al, 1994;Bigazzi et al, 1995). In the isolated heart perfused in the Langendorff apparatus, the perfusion fluid does not enter the left ventricle, hence the coronary flow is substantially independent of cardiac activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the heart, NO may be generated by various components of the coronary vessels, such as endothelium and smooth muscle cells (Palmer et al, 1988;Mollace et al, 1991), as well as by perivascular mast cells (Masini et al, 1991). In this context, it should be mentioned that mast cells and vascular smooth muscle cells have been shown by us to increase NO production upon RLX treatment (Masini et al, 1994;Bigazzi et al, 1995). In the isolated heart perfused in the Langendorff apparatus, the perfusion fluid does not enter the left ventricle, hence the coronary flow is substantially independent of cardiac activity.…”
Section: Discussionmentioning
confidence: 98%
“…In recent studies carried out in our laboratory on mast Author for correspondence. cells (Masini et al, 1994), platelets and arterial smooth muscle cells in culture, RLX has been found to stimulate the production of nitric oxide (NO), which is known to be a powerful vasodilator agent (Ignarro et al, 1987;Palmer et al, 1987). Therefore, we were prompted to search for a relationship between possible changes in coronary flow and NO production by the heart upon RLX administration, and to compare the effects of RLX with those exerted by endothelium-dependent and -independent vasodilator agents.…”
Section: Introductionmentioning
confidence: 99%
“…refl ected in the histopathology and numerous biochemical parameters that require to be assessed in order to arrive to a proper classifi cation of the disease. It has been reported that relaxin can stimulate the nitric oxide pathway or the glucocorticoid receptor [7,14] . In our work we have evaluated the combined vasorelaxing and anti-infl ammatory properties of relaxin on the evolution of acute pancreatitis, our results show that relaxin plays a highly beneficial role when administered within the first hour of the initiation of the noxa being this even more pronounced when the drug was given 1h pre and 4h post triggering acute pancreatitis, this would be particularly relevant for the prevention of post-ERCP pancreatitis providing basis for future studies where combined drug treatments can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that relaxin up regulates nitric oxide synthase (NOS) II expression thus inducing nitric oxide mediated vasodilatation by a controlled activation of endogenous nitric oxide biosynthesis [11] . By regulating nitric oxide relaxin inhibits neutrophil extravasation, adhesion, recruitment and activation [12] ; decreases the expression of chemokines and adhesion molecules [13] ; inhibits histamine release by mast cells [14] ; depresses platelet aggregation [15] ; alters Ik-B phosphorylation and degradation diminishing NF-kB activation and binding to DNA and enhances the activation of the glucocorticoid receptor (GR) [16] . Therefore, via the nitric oxide pathway relaxin exerts vasorelaxant, anti-thrombotic and anti-infl ammatory properties.…”
Section: R E L a X I N P R E V E N T S T H E D E V E L O P M E N T O mentioning
confidence: 99%
“…Concerning the mechanism of action of RLX on its target organs, our studies of coronary vessels in the isolated, perfused rat and guinea pig heart 7,8 have shown that the vasodilatory action of RLX is mediated by stimulation of endogenous production of NO, which is a powerful vasorelaxant. 11,12 It is worth noting that stimulation of intrinsic NO production is also involved in the response to RLX in different cells, such as rat and guinea pig serosal mast cells, 13 human and rabbit platelets, 14 and mammary adenocarcinoma MCF-7 cells. 15 There is general agreement that the vasodilatory action of NO is primarily an endothelium-dependent process.…”
mentioning
confidence: 99%